2019
DOI: 10.1542/peds.2019-0338
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Concentrate Use in Adolescents

Abstract: BACKGROUND: Cannabis concentrates, which are cannabis plant extracts that contain high concentrations of D-9-tetrahydrocannbinol (THC), have become increasingly popular among adults in the United States. However, no studies have reported on the prevalence or correlates of cannabis concentrate use in adolescents, who, as a group, are thought to be particularly vulnerable to the harms of THC. METHODS: Participants are a racially and ethnically diverse group of 47 142 8th-, 10th-, and 12thgrade students recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 54 publications
2
28
1
1
Order By: Relevance
“…With legalization, there are business reasons to increase THC concentration, and new cultivars are being grown that have potency as high as 30%. Cannabis concentrate, made by extracting THC from the marijuana plant, may have a THC content ranging from 39% to 69% (Meier et al, 2019). Cannabinoids are not regulated or approved by the U.S. Food and Drug Administration (FDA), with the exception of one prescription CBD medication and two prescription THC products.…”
Section: Potency/contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…With legalization, there are business reasons to increase THC concentration, and new cultivars are being grown that have potency as high as 30%. Cannabis concentrate, made by extracting THC from the marijuana plant, may have a THC content ranging from 39% to 69% (Meier et al, 2019). Cannabinoids are not regulated or approved by the U.S. Food and Drug Administration (FDA), with the exception of one prescription CBD medication and two prescription THC products.…”
Section: Potency/contaminantsmentioning
confidence: 99%
“…There are many routes of exposure for cannabinoids including smoking the flowers and leaves, vaping concentrates, applying a vaporized spray to the buccal area, ingesting capsules, liquids, or foods and applying topical lotions. Potency and timing of effects on the user vary greatly according to method used (Meier, Docherty, Leischow, Grimm, & Pardini, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Children are especially vulnerable to cannabis poisoning due to their metabolism and lower body weight. 6,7 Other contributing factors…”
Section: Introductionmentioning
confidence: 99%
“…The study by Meier et al 6 in this month's issue of Pediatrics, entitled "Cannabis Concentrate Use in Adolescents," is the first report in which rates of use of these highly potent forms of marijuana by adolescents are described. 4 Using a state-wide, ethnically diverse sample of 46 850 middle and high school students (grades 8, 10, and 12) in Arizona, Meier et al 6 found that 33% of students reported lifetime use of any cannabis product, and of these lifetime users, almost three-quarters (72%) had also used concentrates. In addition, they found that those students who reported using concentrates were more likely than cannabis nonusers or cannabis concentrate nonusers to be women, to report using other substances, and to endorse risk behaviors such as rebelliousness and academic failure.…”
mentioning
confidence: 99%
“…Increased efforts to regulate tetrahydrocannabinol concentrates and the delivery systems that teens are using to vape nicotine, flavorings, and marijuana, increase the minimum mandatory age to purchase all e-cigarette products to 21 years, and restrict marketing and advertising aimed at adolescents are clearly warranted. Additional research and reports such as that by Meier et al 6 may be the impetus needed to bring about much-needed oversight, education, and regulation. ABBREVIATION E-cigarette: electronic cigarette…”
mentioning
confidence: 99%